O cadáver como um recurso do poder: racionalizando algumas narrativas político-criminais - Gennari, Patrícia Visnardi (2022)
The human body shows complex axiological manifestations, even after death. We sought to unveil the epistemological plans that affect this study by a rational way, so that it would be possible to verify to what extent the corpse was or is used as a resource of power, whether in the political, scientific or state punitive power. The choice for the guaranteeist methodology (by Luigi Ferrajoli) was due to the autonomy of the Moral from Law and its the “reasons” of criminal law. Despite the findings of a (necro)political order, the theme is parallel to the very development of the power to punish, which gave rise to the examination the criminal policy movements, searching the levels of guarantees involved. Amid such reflections, it was necessary to carry out a dogmatic approach, in order to equalize the axiology and epistemology then developed, so that we could then face up to our Brazilian legal system and its behavior with the power narratives involved